Accident prevention via information transfer from vehicles to pedestrians based on visual functions of velocity perception. Issue 1 (31st December 2022) - Yokoya, Yasuhi; Soma, Hitoshi
Abstract: To prevent potentially dangerous decisions made by pedestrians while crossing roads, this paper presents an examination of the information that needs to be effectively conveyed from a vehicle to the pedestrians. We studied the information required by the pedestrians to maximize the distance at which they can perceive the velocity of the vehicle, and we examined where to display this information. We used a visual model that is capable of analysing and obtaining the tangential and normal components of vehicle velocity from 2D polar coordinates, with the pedestrian's eyeball as the origin. In this model, the velocity components contributing to the maximum distance at which the speed is detectable are determined by the pedestrian eye level, overall vehicle height, and perception threshold for each velocity component. It was shown that if the tangential velocity component contributes, displaying the vehicle-location in the visual field by showing the dividing line between the vehicle and the road surface can be useful. If the normal component contributes, it can be effective to display the vehicle's frontal area by showing the dividing line between the vehicle and the background. These findings can provide the requirements of the effective provision of information that prevents pedestrian accidents.